Biotransformation of trace organic compounds by activated sludge from a biological nutrient removal treatment system. (September 2016) - Inyang, Mandu; Flowers, Riley; McAvoy, Drew; Dickenson, Eric
Highlights: Simultaneous removal of a suite of TOrCs in BNR treatment was investigated at the bench-scale. Biodegradation of TOrCs was modeled using pseudo-first order kinetics. Most TOrCs showed highest removal within the aerobic zone. Biotransformation of some TOrCs occurred in anoxic and anaerobic zones. Abstract: The removal of trace organic compounds (TOrCs) and their biotransformation rates, kb (L gSS − 1 h − 1 ) was investigated across different redox zones in a biological nutrient removal (BNR) system using an OECD batch test. Biodegradation kinetics of fourteen TOrCs with initial concentration of 1–36 μg L − 1 in activated sludge were monitored over the course of 24 h. Degradation kinetic behavior for the TOrCs fell into four groupings: Group 1 (atenolol) was biotransformed (0.018–0.22 L gSS − 1 h − 1 ) under anaerobic, anoxic, and aerobic conditions. Group 2 (meprobamate and trimethoprim) biotransformed (0.01–0.21 L gSS − 1 h − 1 ) under anoxic and aerobic conditions, Group 3 (DEET, gemfibrozil and triclosan) only biotransformed (0.034–0.26 L gSS − 1 h − 1 ) under aerobic conditions, and Group 4 (carbamazepine, primidone, sucralose and TCEP) exhibited little to no biotransformation (<0.001 L gSS − 1 h − 1 ) under any redox conditions. BNR treatment did not provide a barrier against Group 4 compounds.